Contrast enhanced mammography (CEM) versus magnetic resonance imaging (MRI) for staging of breast cancer: The pro CEM perspective. Issue 142 (September 2021) - Lobbes, M.B.I.; Heuts, E.M.; Moossdorff, M.; van Nijnatten, T.J.A.
Highlights: CEM is able to assess breast cancer extent as accurately as MRI. For assessing axillary nodes, US has equal diagnostic performance as breast MRI. 'Missing' internal mammary lymph node metastases has limited consequences. MRI remains the preferred imaging modality for a select group of women. In all other sub groups, CEM can be considered for preoperative staging. Abstract: In women with newly diagnosed breast cancer, preoperative staging is required to assess disease extent, enabling us to decide on the most optimal treatment strategy. For locoregional staging, assessment of intramammary tumor extent and presence of axillary and perhaps also internal mammary lymph node metastases is required. Due to the similarity in the underlying principle, contrast-enhanced mammography is increasingly considered instead of breast MRI for this purpose. When considering the combination of CEM and US as a single appointment imaging strategy for preoperative staging of breast cancer, there is only limited room for an additional benefit of breast MRI. For tumor size measurements, equal performance of both CEM and MRI are observed. Sensitivity of both techniques for detecting breast cancer is comparable, meaning that both techniques are capable of detecting additional ipsilateral or contralateral tumor foci. However, specificity is in favor of CEM, meaning that there is a slightly lower chance of having false positive findings in preoperative staging of the breast. Axillary US can be performed during the same appointment as CEM, with equal performance and limitations as evaluation of the axilla on standard breast MRI examinations. Finally, there is no need to actively pursue the detection of IMLN metastases, meaning that additional MRI to do so is not required. This review provides a 'pro-CEM' perceptive on the arguments why breast MRI is hardly necessary when CEM in combination with US has been performed as a single appointment imaging strategy in breast cancer patients.